(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
This article explores the role of metaphors and metonymies in advertising and focuses on how these cognitive mechanisms function in tandem in a process known as parallel chaining. Drawing on the principles of Cognitive Linguistics, the article highlights how metaphor and metonymy can reinforce brand messaging, guide consumer perceptions and avoid explicit claims – particularly in products such as tobacco or sweetened beverages which have been proven to be harmful to health or are legally restricted. The concept of parallel chaining has been adapted from Goossens (2003) and Sullivan (2007) and illustrates how metaphor and metonymy operate side by side and enhance the impact of an advertisement. Through both verbal and visual examples of Coca-Cola’s Open Happiness campaign, Nike’s Run the day slogan, and Red Bull Gives You Wings slogan, the article demonstrates how advertisements use layered conceptual mappings to evoke emotions or shape consumer behaviour. In addition, the article examines how this process extends to visual advertising in commercial or political campaigns. The article stresses the significance of parallelly chained metaphors and metonymies in making advertisements more persuasive and appealing to a more diverse audience.